Prevalence of hypercalcemia among cancer patients in the United States. (5th June 2016) - Gastanaga, Victor M.; Schwartzberg, Lee S.; Jain, Rajul K.; Pirolli, Melissa; Quach, David; Quigley, Jane M.; Mu, George; Scott Stryker, W.; Liede, Alexander
Abstract: Hypercalcemia of malignancy (HCM) is a serious metabolic complication whose population‐based prevalence has not been quantified. Rates of HCM differ by tumor type, with highest rates reported in multiple myeloma and lowest among colorectal and prostate cancer patients. This analysis estimates HCM prevalence in the US. This retrospective study used the Oncology Services Comprehensive Electronic Records (OSCER) warehouse of electronic health records (EHR) including laboratory values from 569000 patients treated at 565 oncology outpatient sites. OSCER data were projected to the national level by linking EHR to claims data. Cancer patients included were ≥18 years, and had serum calcium (Ca) and albumin (for corrected serum Ca [CSC]) records. Period prevalence was estimated by HCM CTCAE grade, tumor type, and year (2009–2013). Estimates were adjusted to capture patients diagnosed with HCM outside oncology practices based on a subset of patients linkable to office and hospital data. The analysis included 68023 (2009) to 121482 (2013) cancer patients. In 2013, patients with HCM had a median of six Ca tests, 69.7% had chemotherapy, and 34% received bone modifying agents. HCM rates were highest for multiple myeloma patients (7.5% [2012]–10.2% [2010]), lowest for prostate cancer (1.4% [2012]–2.1% [2011]).The estimated adjusted annual prevalence of HCM from 2009 to 2013 was 95441, 96281, 89797, 70158, and 71744, respectively. HCM affected 2.0–2.8% of all cancer patients. EHR data from oncology clinics were critical for this study because these data contain results from laboratory studies (i.e., serum calcium values) that are routinely ordered in that setting. We estimated that the prevalence of HCM in the US in 2013 is 71744, affecting approximately 2% of cancer patients overall. This percentage differs by tumor type and appears to have decreased over the five‐year study period. Abstract : Hypercalcemia of malignancy (HCM) is a serious metabolic complication whose population‐based prevalence has not been quantified, although rates differ by tumor type. This retrospective study used electronic health records including laboratory values from 569000 patients treated at 565 oncology outpatient sites to provide prevalence estimates in the United States. Our results estimated that the prevalence of HCM in 2013 was 71744, affecting approximately 2% of cancer patients overall, varying by tumor type, and it appears to have decreased over the 5‐year study period.